The role of actin bundling proteins in the assembly of filopodia in epithelial cells - Khurana, Seema (Landes Bioscience, 2011)
The goal of this review is to highlight how emerging new models of filopodia assembly which include tissue specific actin-bundling proteins could provide more comprehensive representations of filopodia assembly that would describe more adequately and effectively the complexity and plasticity of epithelial cells. This review also describes how the true diversity of actin bundling proteins must be considered to predict the far-reaching significance and versatile functions of filopodia in epithelial cells.